(M+3)-2m=3(m-3)

Simple and best practice solution for (M+3)-2m=3(m-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (M+3)-2m=3(m-3) equation:


Simplifying
(M + 3) + -2m = 3(m + -3)

Reorder the terms:
(3 + M) + -2m = 3(m + -3)

Remove parenthesis around (3 + M)
3 + M + -2m = 3(m + -3)

Reorder the terms:
3 + M + -2m = 3(-3 + m)
3 + M + -2m = (-3 * 3 + m * 3)
3 + M + -2m = (-9 + 3m)

Solving
3 + M + -2m = -9 + 3m

Solving for variable 'M'.

Move all terms containing M to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + M + -3 + -2m = -9 + -3 + 3m

Reorder the terms:
3 + -3 + M + -2m = -9 + -3 + 3m

Combine like terms: 3 + -3 = 0
0 + M + -2m = -9 + -3 + 3m
M + -2m = -9 + -3 + 3m

Combine like terms: -9 + -3 = -12
M + -2m = -12 + 3m

Add '2m' to each side of the equation.
M + -2m + 2m = -12 + 3m + 2m

Combine like terms: -2m + 2m = 0
M + 0 = -12 + 3m + 2m
M = -12 + 3m + 2m

Combine like terms: 3m + 2m = 5m
M = -12 + 5m

Simplifying
M = -12 + 5m

See similar equations:

| 5x+67=180 | | 25x^2+30x=-9 | | 4(-4x+4)=208 | | -2x^3y+4x^2y^2+70xy^3=0 | | -15-(-2)-(11-6)= | | 4+4x=-7x-40 | | 210=10*w*3 | | 2u+18=7(u+4) | | x-5+x-5+x-5+x-5= | | 136=x^2+16X | | -10-9x=-8x+7 | | -8x+4(x-8)=-36 | | -x*6=-18 | | 3x=4-7x^2 | | 9x+7=180 | | 108+4y=-2y | | (x)+(x+2)=33 | | 6y+3=6-2y | | 5p+d*r=r-7 | | 6x-10=-70-4x | | 5(2x+61x+294)=0 | | 10+3y=0 | | 9x-10x-17=7 | | 8d=-6 | | X-49=12 | | 2x^5+250x^2=0 | | -x+9=-27 | | 5(n+6)+24=-9 | | 54h^2-24k^2=0 | | 3m^2=4m-1 | | x^2-8x+93x-2= | | (-5+i)(-5-i)= |

Equations solver categories